FEMINISM PORTRAYED IN THE MAIN CHARACTER OF MOVIE MALEFICENT 2 MISTRESS OF EVIL : FEMINISM PORTRAYED IN THE MAIN CHARACTER OF MOVIE MALEFICENT 2 MISTRESS OF EVIL - Gusti Ayu, Krisna dewi; I Made Iwan Indrawan Jendra; I Komang Sulatra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
Abstract Feminism is manifested worldwide and it is represented by various institutions committed to activity on behalf of women's rights and interests. This study used maleficent 2 mistress of evil movie by Robert Stromberg. In this movie there is nine main character there are Maleficent, Aurora, Prince Phillip, Diaval, Queen Ingrith, King John, Conall, and Borra. This study has two aims: (1) to identify the types of feminism depicted in the movie through the main characters, and (2) to analyze how the characters died fighting for their rights. The study was based on Tong's (1998) theory, and the data has been collected by watching the movie repeatedly. To observe the main characters' conversation, a descriptive study and textual analysis have been used. According to the findings of this study, liberal feminism is the most often portrayed type of feminism. The main characters in the story struggled to gain independence and their rights. Maleficent and Aurora were successful in uniting two kingdoms and bringing the moors and people together in peace and happiness. This study used the documentation method to collect the data and the method used in analyzing data was qualitative.